Zinc(II) complexes of azadipyrromethene: Effect of nature and placement of solubilizing groups on structural, thermal, electrochemical and optical properties. (December 2022) - Jimenez, Jayvic C.; Tran, Quynh; Pugh, Madison H.; Brancel, Christina D.; Rheingold, Arnold L.; Sauvé, Geneviève
Abstract: Zinc(II) complexes of azadipyrromethenes are non-planar chromophores with strong absorption in the visible to NIR and are promising n-type materials for organic solar cells. To increase solubility and tune their properties, we incorporated hexyl or hexyloxy solubilizing groups either on the distal or proximal phenyls of bis [2, 6-diphenylethynyl-1, 3, 7, 9-tetraphenyl azadipyrromethene] zinc(II) (Zn(WS3)2 ). Crystal structures confirm the typical distorted tetrahedral geometry for these types of complexes and show that the solubilizing groups on the distal phenyls extend away from the conjugated core whereas groups on proximal phenyls interact with the other ligand. Differential scanning calorimetry measurement indicated that crystals of distal-substituted complexes have two endothermic peaks: solubilizing groups 'melting' and complex melting, whereas the proximal-substituted complexes show one exothermic crystallization peak and one endothermic melting peak. Electrochemical and optical properties varied as expected for ADP-based complexes: the presence of electron rich groups at the proximal substitutions resulted in lower oxidation potentials, higher HOMO levels, red-shifted absorption and lower optical gap than distal substitutions, and the effect was greater for hexyloxy than hexyl. Upon thermal annealing, films of the hexyloxy-substituted complexes strongly aggregated and showed crystal features under a polarized microscope, indicating that hexyloxy groups drive ordered self-assembly, especially when placed on distal phenyls. The ability to guide solid-state self-assembly of these non-planar chromophores using solubilizing groups have the potential to improve their charge carrier mobility and performance in opto-electronic applications such as organic solar cells, and photodetectors. Graphical abstract: Image 1 Highlights: Zinc(II) complexes of azadipyrromethenes are chromophores with non-planar geometry. Solubilizing groups on the proximal phenyls overlap with other ligand. Solubilizing groups on the distal phenyls extend away from core. Hexyloxy groups drive ordered self-assembly in films. The effect is stronger if placed on the distal phenyls than on proximal phenyls.